Comparing Bulgarian and Greek policies for the integration of Turkish/muslim minorities: The cold war period - Korkmaz, Nuri (Ahmet Yesevi University bilig@yesevi.edu.tr, 2019)
Comparing political approaches toward Turkish/Muslim minorities in Bulgaria and Greece became a necessity in order to examine the integration of minority groups under different conditions. This study focuses on the policies of integration of ethnic/religious minorities in Bulgaria and Greece during the Cold War period, studies various methodologies adopted by the communist rule in Bulgaria and the liberal democratic rule in Greece. Since Turkish/Muslim minorities in Bulgaria and Greece claim Turkey as their kin-state, the study partially reflects the perception of minority groups by the majority. Several factors such as educational policies, religion and political approaches to integrate minorities have been evaluated in order to give an overview on the peculiarities and similarities in both cases that are compared. There is detailed analysis also on the issue of national identities and how their conditionality has been defined with the co-existence of minority groups in Bulgaria and in Greece. © 2019, Ahmet Yesevi University. All rights reserved.
Bulgaristan ve yunanistan’ın müslüman-Türk azınlığın entegrasyonuna yönelik politikalarının karşılaştırmalı incelemesi: Soğuk savaş dönemi
Keywords: Bulgaria; Communism; Comparative policy analysis; Democracy; Greece; Turkish minority; Western Thrace